Rib Fixation for a Patient with Severely Displaced and Overlapped Costal Cartilage Fractures - Sung Ho Han; Soon-Ho Chon; Jong Hyun Lee; Min Koo Lee; Oh Sang Kwon; Kyoung Hwan Kim; Jung Suk Kim; Ho hyoung Lee (Journal of Trauma and Injury)
Rib fixations for flail chest or displaced rib fractures are not a new technique. However, reports on rib fixations involving costal cartilage fractures are very few and surprisingly there are no reports of internal fixations involving only the costal cartilage in the English literature. The diagnosis is difficult and the necessity of the procedure may be quite controversial. Placing plates in screws into the costal cartilage alone may seem unstable and easily dislodged or stripped through the cartilage. We report a 31-year-old male scuba diver instructor who underwent rib fixations over his 7th and 8th costal cartilage ribs for severe pain. The procedure was done with conventional plates and screws. He had the plates and screws removed 2 months later due to lingering pain, but with them removed he is now quite happy with the results without pain. The procedure for fixation of painful overlapped costal cartilage is quite simple and can be done with the usual conventional methods, fixating plate and screws directly over the cartilage alone without fixation over the bony rib.